KONTEN MARKETING INSTAGRAM DAN BRAND IMAGE PADA MINAT PENGGUNAAN JASA PERENCANA KEUANGAN - Muhamad Mirzan Hasan Bisri; Pitoyo Pitoyo (Jurnal Pustaka Komunikasi, 2022)
In marketing and developing a product, companies must have a strategy on how brands can be recognized, communicated and get product positioning in the market through digital promotions using electronic media, one of which is Instagram social media, which in turn will affect interest in using products or services. . This study aims to determine the effect of marketing content and brand image as a mediation on interest in using financial planning services Finansialku.com. The test tool used is SMART PLS 3.0. The results showed that the marketing content variable had a significant effect on brand image and interest in using, and the brand image variable had a significant influence on interest in using services, as evidenced by the partial test or t-test showing the P Values below 0.05. Likewise, the path analysis test shows the results that brand image mediates between marketing content variables and interest in using the services of financial planners at Financialku.com as evidenced by P Values below 0.05.